The influence of e-commerce seller reverse logistics quality on customer loyalty: The mediating role of customer experience and perceived value - Gronphet, Seree; Onputtha, Suraporn (Edelweiss Applied Science and Technology, 2025)
In the era of highly competitive e-commerce business, the quality of reverse logistics plays an important role in customer experience and customer loyalty. This research aimed to study the relationship between reverse logistics quality, customer experience, value perception, and customer loyalty by collecting data from 400 consumers who have experience in purchasing and returning products via e-commerce platforms. The data analysis used the Structural Equation Modeling (SEM) technique. The results of the hypothesis testing found that the quality of reverse logistics has no direct effect on customer loyalty, but it has an indirect effect through the mediating variables: customer experience and value perception. In addition, the analysis results indicated that the quality of reverse logistics has a significant positive effect on customer experience and perceived value, whereby customers who have a good experience in returning products are more likely to perceive the value of the service and be more loyal to the seller. These findings suggest that sellers should focus on improving the reverse logistics process to be transparent, convenient, and less disruptive to customers to enhance their competitiveness in the e-commerce market.